Modelling of the Interrelationships Between Population Sex Ratio and Food Content and Ecological Niches in the Marine Lampreys - Yang, Xinxin; Ren, Huitao; He, Jiaxin (Transactions on Environment, Energy and Earth Sciences, 2024)
In this paper, a model related to sex ratio and food content was developed and solved. Through logistic function fitting, it was found that the sex ratio of the Marine lampreys was affected by environmental conditions, with approximately 56% males when food was plentiful and up to 78% when conditions changed. A correlation function model between sex ratio and food content was developed and the normality and absence of autocorrelation of the model was verified by residual analysis (Shapiro-Wilk and Durbin-Watson tests).In order to further explore the interrelationships between sea sevengill eels and their ecological niches, this paper extends the classical Lotka-Volterra model to include competitor and predator equations, and analyses the changes of the various populations under the initial conditions by numerical simulations. Through Spearman correlation analysis, it was found that sex ratio significantly affects the number of predators, competitors and prey in the ecosystem, where an increase in the proportion of males suppresses the growth of the number of prey and competitors, and promotes the increase of the number of predators.